LINGKUNGAN FISIK, PEMBERANTASAN SARANG NYAMUK 3M PLUS DAN DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS PAYUNG SEKAKI : Physical Environment, Eradication Mosquito Nest 3M Plus, and Dengue Hemorrhagic Fever (DHF) in Payung Sekaki Health Center - Irawan, Angki; Suryati, Elfia (Poltekes Kemenkes Tanjungpinang, 2021)
DHF Â is one of the public health problems in Indonesia that the number of sufferers tends to increase and its spread is increasingly widespread. Payung Sekaki district Â is the place with the highest cases in the city of Pekanbaru as many as 145 cases and 1 person died. The study aimed to identify the physical environment, 3M Plus mosquito eradication of dengue hemorrhagic fever (DHF) in Payung Sekaki health center. This type of research is a quantitative study with cross sectional study. The research used survey and interview methods. The sampling technique used simple random sampling. Data collection was carried out by interview and observation with sample size of 194 household. The results showed that there is a meaningful relationship between wells dug (p value= 0.001), water reservoirs (p value= 0.005), close water reservoirs (p value= 0.004), installation of gauze wire (p value= 0.001), and there is no meaningful relationship between the habit of hanging clothes (p value= 0.108), drain water reservoirs (p value = 0.288), burying used goods ( pvalue = 0.941) with the incidence of dengue hemorrhagic fever in Payung Sekaki Health Center. It is expected that the public health center and cadres will further increase counseling activities on 3M Plus activities and environmental hygiene in payung sekaki health center.